2020
DOI: 10.1017/s0967199420000337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen concentrations on developmental competence and transcriptomic profile of yak oocytes

Abstract: Summary Oxygen concentration influences oocyte quality and subsequent embryo development, but it remains unclear whether oxygen concentrations affect the developmental competence and transcriptomic profile of yak oocytes. In this study, we investigated the effects of different oxygen concentrations (5% versus 20%) on the developmental competence, reactive oxygen species (ROS) levels, glutathione (GSH) content, and transcriptomic profile of yak oocytes. The results showed that a low oxygen concentration sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The sequencing of the yak genome was first published in 2012 [26], which laid an important foundation for subsequent yak−related studies. Among the previous studies on hypoxia−adapted transcription in yaks, most of the previous studies on the transcriptome of yaks (Bos grunniens) focused on reproduction and nutrition [27][28][29][30]. The studies on the lung transcriptome of high−altitude yaks and low−altitude cattle (Bos taurus) focused on exploring the potential mechanisms of yak adaptation to high−altitude environments [25,26,31,32], but no studies have ever been conducted at the cellular level to reveal the mechanism of yaks' adaptation to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing of the yak genome was first published in 2012 [26], which laid an important foundation for subsequent yak−related studies. Among the previous studies on hypoxia−adapted transcription in yaks, most of the previous studies on the transcriptome of yaks (Bos grunniens) focused on reproduction and nutrition [27][28][29][30]. The studies on the lung transcriptome of high−altitude yaks and low−altitude cattle (Bos taurus) focused on exploring the potential mechanisms of yak adaptation to high−altitude environments [25,26,31,32], but no studies have ever been conducted at the cellular level to reveal the mechanism of yaks' adaptation to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the antioxidant mechanism is not carried out smoothly, increased ROS could lead to RNA damage [ 59 ]. Further, several studies have demonstrated that HO concentrations induce imbalance between ROS generation and ROS scavenging in live cells [ 55 , 60 , 61 ]. In our study, blastocysts cultured under DO exhibit significantly higher mRNA levels of 16 s rRNA compared with that in the HO group.…”
Section: Discussionmentioning
confidence: 99%
“…The oocyte cleavage rate of in-vitro-fertilized embryos also increased. Among these three antioxidants, cysteamine had the strongest effect on the increase of GSH content in oocytes [100].…”
Section: Antioxidantsmentioning
confidence: 97%